A Review of Fatty Acid Biosynthesis Enzyme Inhibitors as Promising Antimicrobial Drugs - Laurie Bibens; Jean-Paul Becker; Alexandra Dassonville-Klimpt; Pascal Sonnet (MDPI AG, 2023)
Resistance to antimicrobial drugs is currently a serious threat to human health. Consequently, we are facing an urgent need for new antimicrobial drugs acting with original modes of action. The ubiquitous and widely conserved microbial fatty acid biosynthesis pathway, called FAS-II system, represents a potential target to tackle antimicrobial resistance. This pathway has been extensively studied, and eleven proteins have been described. FabI (or InhA, its homologue in mycobacteria) was considered as a prime target by many teams and is currently the only enzyme with commercial inhibitor drugs: triclosan and isoniazid. Furthermore, afabicin and CG400549, two promising compounds which also target FabI, are in clinical assays to treat Staphylococcus aureus. However, most of the other enzymes are still underexploited targets. This review, after presenting the FAS-II system and its enzymes in Escherichia coli, highlights the reported inhibitors of the system. Their biological activities, main interactions formed with their targets and structure-activity relationships are presented as far as possible.